Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Siswa Tentang Penyakit Menular Seksual di SMA Nusantara Indah Sintang - Antonius Antonius; Elvi Juliansyah; Hendrikus Nara Kwureh (VISIKES: Jurnal Kesehatan Masyarakat, 2018)
Adolescence is a time of self-discovery that encourages him to have a high curiosity and have complex problems. One is a sexually transmitted disease. Factors that cause the occurrence of sexually transmitted diseases in adolescents is the lack of information and knowledge about sexually transmitted diseases. Research To determine the effect of health education on the knowledge and attitude of students about sexually transmitted diseases in senior high school Nusantara Indah Sintang District in 2018. Quantitative research with Pre Experimental approach, the planning used is One Group Pre test and Post test.Rresearch shows T-test paired sample with P value = 0,000 <0,05 this indicates that there are differences before and after health education on students' knowledge and attitudes about sexually transmitted diseases. Health education influences students' knowledge and attitude about sexually transmitted diseases in senior high schoolÂ  Nusantara Indah Sintang 2018. Health education on sexually transmitted diseases should be continued to improve knowledge and change the attitude of students in adolescence.